Periodontitis-induced neuroinflammation triggers IFITM3-Aβ axis to cause alzheimer’s disease-like pathology and cognitive decline - Lingwenyao Kong; Juanjuan Li; Lu Gao; Yonggang Zhao; Weixian Chen; Xumeng Wang; Songlin Wang; Fu Wang (Alzheimer’s Research & Therapy)
Abstract Background Periodontitis is a risk factor linked to Alzheimer’s disease (AD), and characterized by amyloid-beta (Aβ) pathology. Mounting evidence suggests a contributory role of periodontitis in the onset and progression of AD. Type I interferons are upregulated in Porphyromonas gingivalis (Pg)-induced periodontitis in murine models. Colonization of Pg has been identified in the brains of patients with AD. Recently, interferon-induced transmembrane protein 3 (IFITM3), an inflammation-induced innate immunity protein, was identified as a novel γ-secretase modulatory protein for Aβ production in AD. However, whether periodontitis triggers an increase in type I interferons in the brain, subsequently inducing AD-like pathology by eliciting the innate immune response of glial cells and activating the IFITM3-Aβ axis, remains unclear. Additionally, the question of whether colonization of Pg in brain induces innate immune in astrocytes and microglia remains unanswered. Methods We assessed the impact of Pg-induced periodontitis on cognitive impairment in C57BL/6J and APP/PS1 mice using behavioral tests. The effects of Periodontitis/Pg on microglia and astrocytes were measured using quantitative reverse transcriptase PCR (qRT-PCR), western blotting, and histological staining. Results Pg-induced periodontitis led to cognitive impairment in C57BL/6J mice and exacerbated a cognitive decline in APP/PS1 mice. Furthermore, Pg-induced periodontitis elevated the levels of interferon (IFN)-β, IFITM3, and Aβ deposition in the brains of both C57BL/6J and APP/PS1 mice. We also identified Pg DNA, glial activation, and the expression of inflammatory mediators in the brain of a Pg-induced periodontitis model. Additionally, our findings confirmed astrocytes as the primary responders to Pg-induced innate immunity and inflammation both in vitro and in vivo. Periodontitis also induces an increase in IFITM3 expression in periodontal tissue, salivary glands. Conclusions We define a previously unidentified link between periodontitis and cognitive decline, and provide new evidence linking oral pathogenic bacteria-induced innate immunity and neuroinflammation to AD pathogenesis and cognitive decline, partly through increased blood-brain barrier (BBB) permeability, triggered neuroinflammation, and elevated IFITM3 in glial cells for Aβ deposition. Moreover, periodontitis exacerbates innate immunity and cognitive impairment in AD mice, underscoring the importance of preventive and therapeutic strategies for periodontal disease in AD patients.